The Education of Children Under Seven (RLE Edu C). - Sturt, Mary (Routledge library editions. Education., 2012)
This book does not cover the whole field of Infants' Teaching but is concerned mainly with general principles and matters which are open to the non-specialist. Some technical subjects such as Physical Education have been omitted but nonetheless the volume provides a thorough (if somewhat dated) introduction to early years education in the first half of the twentieth century.